Pendampingan pemasaran UMKM berbasis digital melalui website marketing - Petaya, Linna Jalin; Trishananto, Yudha; Kumalasari, Yuni; Mualifah, Mualifah; Hastuti, Rizki Dwi; Lestari, Anisa (Tintamas: Jurnal Pengabdian Indonesia Emas, 2024)
service aims to empower MSMEs in Sukoharjo Village, Semarang, through digital marketing assistance with a marketing information provider website. Digital technology is key in advancing MSMEs, especially with the spread of online and offline markets. However, many MSME players have not fully utilized the presence of these online markets. Assistance is carried out through the creation of a website that provides features such as online marketing guides/articles, community forums, tutorials, and support services, where the website helps provide various information about online marketplace platforms, such as Tokopedia, Shopee, Alibaba, Amazon, and so on. The PAR method involved the local community and MSME producers in Sukoharjo Village. This website is expected to increase the visibility and sales turnover of MSMEs in Sukoharjo Village and help them compete in an increasingly competitive market, especially in the online world, domestically and internationally. With this approach, MSMEs can access more market opportunities online, improve their business sustainability, and contribute to local economic growth.